Association Between Meibomian Gland Testing and Ocular Surface Sensitivity. Issue 10 (October 2015) - Cox, Stephanie M.; Nichols, Jason J.
Abstract : Purpose: To assess whether corneal sensitivity is associated with clinical tests assessing the tear film and meibomian glands. Methods: Subjects were recruited based on the history of contact lens wear and the extent of meibomian gland dropout. Clinical examination included assessment of symptoms, redness of the lower eyelid margin, lipid layer thickness, esthesiometry of the inferior cornea and palpebral conjunctiva, noninvasive tear breakup time, Schirmer test assessment, and meibomian gland assessment through orifice count and expressed meibum quality grade. Subjects were grouped into a high corneal sensitivity (HS) group or low corneal sensitivity (LS) group, based on the median sensitivity measure. Groups for palpebral conjunctival sensitivity were created in the same manner. Mann–Whitney U tests were used for comparisons of sensitivity groups, and a Spearman rho correlation coefficient was used to study the associations between each tear film characteristic and the sensitivities. Results: Fifty-seven subjects with an average age of 34.7 years (SD = 15.1) were included in the analysis, of which 63.2% were female. The median corneal and conjunctival thresholds for sensation were 0.5 and 1.4 g/mm 2, respectively. The average noninvasive tear breakup time [HS: 7.8 seconds [interquartile range (IQR) = 5.7]; LS: 11.6 seconds (IQR = 8.4); P = 0.05] and Schirmer test assessments [HS: 16.0 mm (IQR = 15.0); LS: 25.0 mm (IQR = 19.0); P = 0.04] were significantly different between the palpebral conjunctival HS and LS groups. All other group comparisons and correlations were not statistically significant. Conclusions: The palpebral conjunctival sensitivity may be more critical than the corneal sensitivity when assessing dry eye.